The impact of the application of the value-added tax on the financial performance of Saudi joint-stock companies - Alzulfah, Abdulelah Hussin; Gharib, Adel (Journal of Economic, Administrative and Legal Sciences, 2020)
The purpose of this study was to measure the effect of the application of VAT on financial performance in a sample of companies operating in the sectors (retailing of luxury goods, food fragmentation, agriculture and transportation). Linear regression method was used to measure relationship and effect by using STATA in standard analysis and economic models and appreciation.The study found that the financial variables (sales volume, company size, value added tax) accounted for 0.36% of the change in the value of the value added tax. ROA, while 0.64 is the effect of other factors.Based on the results of the study, the study reached several recommendations, the most important of which was to conduct extensive economic studies related to the effect of value added on the indicators of profitability, liquidity and other financial indicators in all Saudi companies so that the results can be generalized. Companies must also develop manufacturing and marketing strategies that mitigate the impact of VAT, so that they can increase sales and maintain their usual profit levels.
Keywords: value added tax; financial performance; net sales; return on assets